Pressure ulcer healing with an intensive nutrition intervention in an acute setting: a pilot randomised controlled trial. (1st September 2020) - Banks, M. D.; Ross, L. J.; Webster, J.; Mudge, A.; Stankiewicz, M.; Dwyer, K.; Coleman, K.; Campbell, J.
Abstract : Objective: To investigate the feasibility of recruitment, retention, intervention delivery and outcome measurement in a nutritional intervention to promote pressure ulcer healing in an acute setting. Method: Some 50 tertiary hospital patients with stage II or greater pressure ulcer were randomised to receive either individualised nutritional care by a dietitian, including prescription of wound healing supplements; or standard nutritional care. Relevant nutritional and pressure ulcer (PU) parameters were collected at day 5, 10, 15, 22 and then weekly or until discharge. Results: The median length of hospital stay was 14 days (1–70) with 29 patients discharged by day 15. There were 24 patients discharged before their PU fully healed. Per cent change in valid PU area and score measures from baseline to day 15 were chosen for outcome data analysis to account for varying initial size and severity of the wound and length of stay. There was a larger percentage reduction in PU measures in the intervention group, but this was not statistically significant. Little difference was found in nutritional intake between the control and intervention groups indicating a requirement to focus on effective delivery of the intervention in future studies. Future studies in the acute setting need to account for length of stay and ideally follow patients until full healing. Conclusion: Results indicate a positive association with nutrition intervention and PU healing and that a rigorously designed and adequately powered study is feasible.